Integrating Education for Sustainable Development into Ecology Learning: Developing a Multimodal E-Book to Enhance Students' Scientific Literacy - Aqilah, Siti; Pursitasari, Indarini Dwi; Rachman, Indriyani; Matsumoto, Toru (Jurnal Pendidikan MIPA, 2025)
The advancement of digital technology has driven innovation in learning resources, including the use of e-books as supportive media in science education. In the context of ecology learning at the junior secondary level, instructional materials are needed that not only present fundamental concepts but also cultivate scientific literacy and sustainability awareness. This study aimed to develop an ecology e-book grounded in the Education for Sustainable Development framework and to examine its feasibility and effectiveness in enhancing students’ scientific literacy. The research employed a Research and Development approach using the ADDIE model, comprising need analysis, design, development, implementation, and evaluation. The e-book was validated by two material experts, two media experts, and twenty science teachers. Validation results showed a very high level of feasibility, with material experts awarding an average score of 96.3 percent and media experts 95.3 percent, supported by a CVI of 0.95 and a CVR of 0.93, indicating strong content validity. During implementation, the e-book’s effectiveness was tested using a quasi-experimental design with 35 students in the experimental class and 27 in the control class. The analysis revealed a moderate improvement in students’ scientific literacy, with an N-gain of 0.43, while the control class achieved an N-gain of 0.20. Gains were evident in knowledge and competency, particularly in understanding scientific phenomena and epistemic reasoning. The distribution of scores in the experimental class also became more homogeneous, suggesting more even conceptual understanding. Statistical tests confirmed significant differences between the two groups, strengthening the evidence of the e-book’s impact. Students’ responses averaged 81 percent in the very good category, covering content, language, visuals, and usefulness. These findings indicate that the ESD-based ecology e-book is feasible and effective for improving scientific literacy among junior secondary students. Keywords: e-book, ecology, education for sustainable development, scientific literacy.